Extended foot-ankle musculoskeletal models for application in movement analysis. Issue 2 (25th January 2017) - Malaquias, Tiago M.; Silveira, Carolina; Aerts, Wouter; De Groote, Friedl; Dereymaeker, Greta; Vander Sloten, Jos; Jonkers, Ilse
Abstract: Multibody simulations of human motion require representative models of the anatomical structures. A model that captures the complexity of the foot is still lacking. In the present work, two detailed 3D multibody foot-ankle models generated based on CT scans using a semi-automatic tool are described. The proposed models consists of five rigid segments (talus, calcaneus, midfoot, forefoot and toes), connected by five joints (ankle, subtalar, midtarsal, tarsometatarsal and metatarsophalangeal), one with 15DOF and the other with 8DOF. The calculated kinematics of both models were evaluated using gait trials and compared against literature, both presenting realistic results. An inverse dynamic analysis was performed for the 8DOF model, again presenting feasible dynamic results.